Laboratory diagnosis of Trypanosoma cruzi infection: a narrative review - Lopez-Albizu, Constanza; Rivero, Rocío; Ballering, Griselda; Freilij, Hector; Santini, María Soledad; Bisio, Margarita María Catalina (Frontiers in Parasitology, 2023)
Trypanosoma cruzi infection, currently endemic in 21 countries, is a public health problem not only in the Americas but also in countries with Latin American migrants. However, it is estimated that two-thirds of people with Chagas disease currently live in urban areas and that only 10% of them are aware of it. This review summarizes the most important aspects of the diagnosis of human T. cruzi infection by describing the following aspects of clinical laboratory diagnosis: the most widely used tests available in Latin America and those expected to improve access to diagnosis of the affected population with their implementation; the advantages, disadvantages, and sensitivity of the tests in the different phases of infection; and their usefulness in the acute or chronic phases of infection and in the context of immunosuppression. In this way, we hope to contribute to broadening the knowledge about this prevalent infection in the Americas.